Lipolytic Markers, Insulin and Resting Fat Oxidation are Associated with Maximal Fat Oxidation - Robinson, S. L.; Chambers, E. S.; Fletcher, G.; Wallis, G. A. (International Journal of Sports Medicine, 2016)
The maximal capacity to oxidize fat during exercise (MFO) is associated with 24-h fat balance and insulin sensitivity. Understanding factors that influence MFO could have implications for metabolic health. We investigated relationships between selected plasma metabolites, hormones and overnight-fasted resting fat oxidation rates (Resting), with MFO. Resting fat oxidation and MFO was measured in 57 men with blood collected at rest and during exercise. Plasma glycerol (R=0.39, P=0.033), non-esterified fatty acids (NEFA: R=0.27, P=0.030) and insulin (R=− 0.36, P=0.007) measured at MFO correlated with MFO; only glycerol remained correlated when controlled for resting concentrations (R=0.36, P=0.008). The change in glycerol from rest to MFO correlated with exercise-induced fat oxidation (R=0.32, P=0.012). V˙O2max correlated with resting fat oxidation (R=0.44, P=0.001) and MFO (R=0.52, P<0.001). Resting fat oxidation correlated with MFO (R=0.55, P<0.001); this remained when controlled for V˙O2max (R=0.41, P=0.001). This study reports weak-to-moderate, albeit significant, relationships between plasma lipolytic markers, insulin and resting overnight-fasted fat oxidation with MFO and shows the plasma glycerol response to uniquely reflect exercise-induced fat oxidation. V˙O2max correlates with fat oxidation but the relationship can be dissociated. Interventions to increase fat oxidation for optimal metabolic health would benefit from, but are not reliant on, increases in V˙O2max.
Keywords: exercise; metabolism; health